Genetic Diversity of Bali Cattle: Cytochrome b Sequence Variation. Issue 1 (May 2019) - Rahmatullaili, Siti; Fatmawati, Diani; Nisa, Choirun; Winaya, Aris; Chamisijatin, Lise; Hindun, Iin
Abstract: Livestock productivity in Indonesia is categorized as low compared to the other countries, yet the local Indonesian cattle is potential to develop. This research aimed to describe the genetic variation and phylogenetic profile of Bali cattle compared to their ancestor, i.e. Bos javanicus based on mitochondrial cytochrome b gene. This research was descriptive in which as many as 11 samples from Bali and 18 samples from Lombok were involved. The data, in term of sequencing results, were analyzed by using MEGA 4 version. The research results showed that the highest variation occurred in sample CL_8 (83 nucleotides), while the lowest one was shown by CB_7 (12 nucleotides). Meanwhile, the phylogenetic tree constructed presented that, genetically, Bali and Lombok cattle were categorized in seven big groups in which the closest genetic distance was between BL_1 and Bos javanicus (0.061), whereas the farthest was the distance between BL_8 and Bos javanicus (0.312). The results of this research can be utilized as the basic data for related fields to determine the most appropriate policies, particularly in managing local cattle breeding to obtain superior filial.